Internet of Things International Workshop, IOT 2012, Changsha, China, August 17-19, 2012. Proceedings - Wang, Yongheng; Zhang, Xiaoming; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the International Workshop on Internet of Things, IOT 2012, held in Changsha, China, during August 17-19. The 95 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on wireless sensor networks; RFID; sensors and equipments; data processing; security; applications and others.
Wireless sensor networks -- RFID -- Sensors and equipments -- Data processing -- Security -- Applications and others.
Keywords: Computer science; Data transmission systems; Computer Communication Networks; Data protection; Information storage and retrieval systems; Computer Science; Input/Output and Data Communications; Computer Communication Networks; Systems and Data Security; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; e-Commerce/e-business.